The History of Medicine and Healthcare Selected Papers - Bolton, Lesley; Pratt, William J.; Stahnisch, Frank W. (Cambridge Scholars Publisher, 2021)
This volume brings together such topics as the history of psychiatry, biomedical ethics in history, military medicine, children, women and changing gender roles in modern medicine, public health history, and a special communication on the history of Canadian hospital workers. Of special note is a paper by internationally renowned historian, Dr Peter L. Twohig, Canadian Research Chair in the History of the Atlantic World at Saint Mary's University in Halifax, Nova Scotia. It is well-illustrated with images and diagrams pertaining to the history of medicine.